The “Pelvic Harness”: a skeletonized mesh implant for safe pelvic floor reconstruction - Natalia,Sumerova (2016)
ABSTRACT Objectives To evaluate the feasibility, safety and surgical results of skeletonized mesh implants to form a pelvic harness for pelvic floor reconstruction surgery. Study design Patients with advanced pelvic floor prolapse were enrolled to this study. Study model was a kit mesh, reduced to 75% of the original surface area by cutting out mesh material from the central mesh body. Patients were evaluated at the end of the 1st and 6th post-operative months and interviewed at the study conclusion. Results Ninety-five women with advanced pelvic floor prolapse had this implant. Mean follow-up duration was 9 months (6-12 months). The POP-Q point’s measurements showed marked and statistically significant improvements. Bladder over-activity symptoms, fecal incontinence, pelvic pain and constipation rates were all reduced as well. No adverse effects related to the dissection or mesh implantation were marked. The first and sixth post-operative month follow-up records as well as the study conclusion interview findings were satisfactory in terms of subjective and objective cure and adverse effects occurrence. Conclusion This study data proposes that skeletonizing meshes might be safely and successfully implanted for potentially improved pelvic floor reconstruction.